URINARY SYSTEM PATHOLOGY IN CHILDREN POPULATION OF KHARKIV REGION: MORBIDITY AND SOME RISK FACTORS - G. R. Muratov; T. F. Kolibaeva; I. V. Sorokina; M. S. Myroshnychenko (Ukrainian Journal of Nephrology and Dialysis, 2015)
Urinary system pathology in children now is one of the most important problems of medical science.The aim of this study – to analyze the morbidity and reveal the risk factors for development of urinary system diseases in children of Kharkiv region.Materials and methods. The material of the study was the information (gender, age, weight and body length at birth, gestational age, clinical diagnosis), obtained during hospitalization of 663 patients aged from 3 months to 17 years in the nephrological center of Kharkiv regional children clinical hospital during the period from 2012 to 2013 years.Results. The authors found that in children population of Kharkiv region among all diseases of urinary system a significant number of cases occur in congenital malformations, dismetabolic nephropathy, urolithiasis.Conclusions. Regional risk factors for development of urinary system pathology in children are female and living in the village. Decreased weight and body length at birth are risk factors for development in children urinary system congenital malformations.